Contractual Clauses to Increase the Remedial Duty - Dill, Amanda Lemos (2025)
This paper aims to address the contractual clauses that intensify the remedial duty, requiring an understanding of its concept and an analysis of the types of conventions that may extend this duty in case of breach of contract. These contractual clauses constitute an exception to the legal provisions of civil liability. Initially, contractual clauses related to the prerequisites for the remedial duty will be examined. Subsequently, contractual clauses that reinforce the guarantee of the obligation and influence the extent of the indemnity will be scrutinized. The objective of this paper is to encourage the systematization of possible contractual clauses that intensify the remedial duty, a topic that has been narrowly studied within Brazilian law.